Abnormal short-latency synaptic plasticity in the motor cortex of subjects with Becker muscular dystrophy: a rTMS study. (1st January 2016) - Golaszewski, Stefan; Schwenker, Kerstin; Bergmann, Jürgen; Brigo, Francesco; Christova, Monica; Trinka, Eugen; Nardone, Raffaele
Highlights: MEP facilitation is reduced in the mentally retarded BMD patients. These findings suggest an altered plasticity in glutamate-dependent circuits. RTMS may shed light on the mechanisms of cortical involvement in dystrophinopathies. Abstract: We used repetitive transcranial magnetic stimulation (rTMS) to further investigate motor cortex excitability in 13 patients with Becker muscular dystrophy (BMD), six of them with slight mental retardation. RTMS delivered at 5 Hz frequency and suprathreshold intensity progressively increases the size of motor evoked potentials (MEPs) in healthy subjects; the rTMS-induced facilitation of MEPs was significantly reduced in the BMD patients mentally retarded or classified as borderline when compared with age-matched control subjects and the BMD patients with normal intelligence. The increase in the duration of the cortical silent period was similar in both patient groups and controls. These findings suggest an altered cortical short-term synaptic plasticity in glutamate-dependent excitatory circuits within the motor cortex in BMD patients with intellectual disabilities. RTMS studies may shed new light on the physiological mechanisms of cortical involvement in dystrophinopathies.